Application of Resonant Nuclear Reactions for Studying the Diffusion of Nitrogen and Silicon in Ti-Modified Stainless Steel. (11th August 2011) - Arunkumar, J.; David, C.; Nair, K. G. M.; Panigrahi, B. K.; Sundar, C. S.
Abstract : Resonant nuclear reaction analysis can be used for the study of diffusion behaviour of minor alloying elements in reactor structural materials. In the present paper, 15 N(p, α γ ) 12 C and 30 Si(p, γ ) 31 P reactions have been used to profile the ion-implanted 15 N and 30 Si in D9 alloy (titanium-modified austenitic stainless steel). The diffusion coefficients at various temperatures have been estimated from the broadening of the implantation profiles during thermal annealing, and the activation energies are deduced.